All-cause and cause-specific mortality rates of patients treated for alcohol use disorders: a meta-analysis - Abdul-Rahman, Abdul-Kareem; Card, Timothy R.; Grainge, Matthew J.; Fleming, Kate M. (Taylor & Francis, 2018)
Background Although alcohol use disorders (AUD) are known to increase the relative risk of all-cause and some cause-specific mortalities, the absolute mortality rates of the AUD population are unknown. Such knowledge would benefit planners of the provision of services for this population, including in prioritising the identification and/or treatment of diseases likely to cause their death. Methods We conducted a systematic review of studies in English, reporting the cause-specific mortality rates among people treated for AUD. Number of deaths by cause, and total person-years of follow-up were extracted. All-cause and cause-specific mortality rates per 1000 person-years were meta-analysed assuming random effects. Results 31 studies were included. Participants were mainly middle-aged males. The quality of studies was generally good. 6,768 all-cause deaths in 276,990.7 person-years of follow-up (36,375 patients) were recorded and the pooled all-cause mortality rate was 27.67/1000 person years (py) (95% confidence interval (CI) 23.9, 32.04). The commonest cause of death in the AUD population was cardiovascular disease (CVD) (6.9/1000py (95%CI 5.61, 8.49)), followed by gastrointestinal deaths (5.63/1000py (95%CI 4.1, 7.74)), unnatural deaths (4.95/1000py (95%CI 4.01, 6.09)), neoplasms, respiratory diseases and substance use disorders. Conclusions Patients with AUD have increased rates of all-cause and cause-specific mortality compared to the general population. Like the general population, they are most likely to die of CVD. In contrast to the general population, gastrointestinal and unnatural deaths are the next most common causes of death. We believe these facts should be considered when planning healthcare services for patients with AUD.